Faktor-Faktor yang Memengaruhi Peningkatan Interdialytic Weight Gain (IDWG) pada Pasien Hemodialisa - Dewin Safitri; Tuti Pahria; Urip Rahayu (Jurnal Keperawatan Silampari, 2022)
This study aims to identify factors that influence the increase in Interdialytic Weight Gain (IDWG) in hemodialysis patients. This research method uses a narrative literature review method by entering keywords into five databases: PubMed, CINAHL, Science Direct, Wiley, and ProQuest. The results showed that the search results obtained 521 articles and ten relevant and qualified articles, then extracted using the DSVIA method. The intrinsic and extrinsic factors that contribute to the increase in Interdialytic Weight Gain (IDWG) in hemodialysis patients. Intrinsic factors include age, gender, knowledge, body mass index, psychological condition, thirst, xerostomia, and self-efficacy. In contrast, external factors (extrinsic) that influence the increase in IDWG are the duration and frequency of hemodialysis, and serum dialysate, including serum sodium and serum creatinine. In conclusion, the rise in Interdialytic Weight Gain (IDWG) can severely impact the patient's condition, so it is necessary to identify the factors that contribute to the increase in interdialytic weight gain plan appropriate nursing actions. Keywords: Hemodialysis, Interdialytic Weight Gain